Implementation of User-Centered Design to Improve User Experience in Patient Queuing System (Case Study: Rs.Al-Irsyad Surabaya) - Anisa Wahyu Ningsih; Naufal Abdillah; Agus Hermanto; Ahmad Habib (Eduvest - Journal of Universal Studies, 2025)
This study aims to improve the user experience and efficiency of the patient queuing system at Al-Irsyad Surabaya Hospital through the implementation of User-Centered Design (UCD). The background highlights the challenges faced by the hospital, including long patient waiting times and low adoption of digital registration due to an unintuitive interface. The research objectives focus on redesigning the system to enhance usability, performance, and security while addressing user needs. A quantitative approach was employed, involving online surveys, iterative prototyping with Figma, and usability testing using the System Usability Scale (SUS) and FURPS++ framework. Key findings revealed that the redesigned application achieved an excellent SUS score of 87, with high functionality (100% success rate in registration), reliability (stable under 50 simultaneous users), and security (AES-256 encryption). Heuristic evaluation identified strengths in "Recognition Rather Than Recall" (score: 4.91) and areas for improvement in "Match Between System and Real World" (score: 4.36). The implications of this research include a 40% reduction in waiting times and increased patient satisfaction, demonstrating the effectiveness of UCD in healthcare digitization. Recommendations for future development include optimizing the interface for small screens and integrating real-time waiting time predictions.